Rethinking literary creativity in the digital age: a comparative study of human versus AI playwriting - Silvia Elias; Bunder Sebail Alshammari; Khaled Nasser Alfraidi; Khaled Mostafa Karam (Humanities & Social Sciences Communications)
Abstract This paper contends that, in the digital era, the creation of art is no longer an endeavor exclusively pursued by humans to achieve a creative product. Over the past decade, computer-generated theater has emerged and progressed significantly through successive projects. This advancement has incited debate about whether these AI-generated works possess literary merit and originality comparable to Human-authored texts. Therefore, this interdisciplinary study aims to draw a comparison between an AI-generated play and a human-authored play in terms of originality, fluency, flexibility, and effectiveness. It utilizes Computational methods and NLP tools to process the two plays, analyze both content and language, and derive quantitative measures that support the creativity assessment of the two plays. The results of content and computational analysis indicate that the human-generated play has higher scores in all indexes of creativity. However, the results also suggest that the AI-generated play features significant creativity potential close in assessment to the human proficiency in several indexes. Thus, AI is capable of creative literary products, though it is not as masterful as those produced by creative humans.